Work Demands and Resources, Stress Regulation and Quality of Pedagogical Work Among Professionals in Finnish Early Childhood Education Settings - Nislin, Mari; Sajaniemi, Nina; Suhonen, Eira; Sims, Margaret; Hotulainen, Risto; Hyttinen, Sirpa; Hirvonen, Ari (Journal of Early Childhood Education Research, 2015)
This study examined early childhood professionals’ (ECPs) stress regulation and the demands and resources they encounter at work, and considered how these factors are associated with the quality of pedagogical work in daycare. The participants were 117 ECPs from 24 daycare centers in the Helsinki metropolitan area, Finland, with data collected using surveys, cortisol measurements, and observational assessments. The results indicated that the professionals generally found their work resources to be adequate and, on average, their stress regulation measured through cortisol activity showed a typical diurnal pattern. Highly important resources at work proved to be support from supervisors, which was associated with stress regulation and the quality of pedagogical work in teams. Although we found only minor associations between cortisol activity and job demands and resources, cortisol activity did relate to pedagogical work, particularly to teamwork; the higher the quality of the teamwork, the lower the ECPs morning cortisol values. Our multidisciplinary study highlights important findings regarding the resources and demands ECPs experience at work, and supports existing literature. In addition, the results demonstrate the importance of social support, especially the role of the supervisor, which proved to be one of the key factors positively enhancing well-being at work. These findings are applicable in planning interventions regarding workrelated well-being among ECPs.
Keywords: stress; cortisol activity; job demands and resources; early childhood education; pedagogical work